Experimental study of natural convection heat transfer in a vertical internally finned tube - Noor Afeeza, Mohamad Sazali (2009)
This paper present an experimental study of a vertical internally finned tube subjected to natural convection heat transfer. All the main parameters that can significantly influence the heat transfer performance of finned tube have been examined. An experimental set-up was designed to study the heat transfer performance in the entrance region as well as in the fully-developed region. I using material called mild steel and its fins are assembly with the body of the cylinder tube internally. The length of tube was 100mm. The inner diameter of tube was 80mm and the outer diameter was 90mm. The tube contains four radial, straight, and equally distributed around the circumference of the tube. The height of the fins are 100mm and the length of the fins are 25mm. Air was used as a working fluid in the experiment. It is found that, unlike expected, the value of Nu for vertical cylinder under variables time varies with the temperature is increasing. Also it is found that the value of Nu increases as the time increases. In this experiment we I using a mild steel as a material for cylinder tube and fins. When mild steel are used and under the conditions of the current experiment no improvement were introduced by using mild steel material. To be conclusive on this result a further experimentations are needed by using aluminum for the cylinder tube material and different length of cylinder tube or its diameter and also using different variables length of fins.